Kinerja Keuangan dan Harga Saham: Studi Pada Perusahaan Pertambangan - Susanti, Ni Komang Rima; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2022)
This study aims to empirically prove the effect of Earnings per Share (EPS), Return On Equity (ROE), Return On Assets (ROA), Net Profit Margin (NPM), Sales Growth (SG), and Book Value per Share (BVPS). on the stock price. The sample in this study was 22 companies from the research population of 49 mining sectors listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used in this research is purposive sampling technique. The data analysis technique used to test the hypothesis is multiple linear regression analysis. Based on the results of the analysis, it can be seen that EPS, ROE, NPM, and SG have no effect on stock prices, while ROA and BVPS have a negative effect on stock prices. Keywords : Financial Performance; Stock Price; Mining Companies.